POPULATION-LEVEL RISK STRATIFICATION AND THERAPEUTIC APPROACHES IN NEONATAL SEPSIS: A HOSPITAL-BASED COHORT ANALYSIS - Dr. M. Swetha; Dr Usha Sree Y; Dr. Shravya Reddy R (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Neonatal sepsis remains a significant contributor to neonatal mortality and morbidity, especially in rural India. Early identification through structured risk stratification can guide therapeutic decision-making and reduce adverse outcomes.Aim: To analyze population-level risk stratification and therapeutic approaches in neonatal sepsis at a rural tertiary care NICU.Objective: To assess population-level risk stratification factors and evaluate therapeutic outcomes in neonates with clinically and microbiologically confirmed sepsis at a rural tertiary care center in Kurnool district. To identify maternal and neonatal risk factors. 2. Determine bacterial etiology and resistance patterns. 3. Evaluate effectiveness of therapeutic interventions. 4. Assess clinical outcomes and mortality predictors.Materials: A hospital-based cohort study was conducted in the Neonatal Intensive Care Unit (NICU) over 18 months. Seventy neonates with sepsis (confirmed by clinical signs and/or blood culture) were enrolled. Risk stratification was performed using demographic, clinical, and laboratory variables. Therapeutic approaches included empirical antibiotic therapy, escalation protocols, and supportive NICU care. Data were analyzed using SPSS v25. Logistic regression was used to identify predictors of adverse outcomes.Results: Of the 70 neonates, 58.6% had early-onset sepsis (EOS), and 41.4% had late-onset sepsis (LOS). Major risk factors included prematurity (47.1%), low birth weight (61.4%), and prolonged rupture of membranes (PROM) >18 hrs (24.3%). Klebsiella pneumoniae (35.7%) and Staphylococcus aureus (28.5%) were the most common pathogens. Empirical antibiotic success rate was 72.8%. Overall mortality was 14.2%, with higher odds among neonates with multiorgan dysfunction and culture-positive sepsis (p